Habitat use and movements of a large dragonfly (Odonata: Anax imperator) in a pond network. (22nd October 2020) - Minot, Marceau; Besnard, Aurélien; Husté, Aurélie
Abstract: Local movements of aquatic insects within the surroundings of waterbodies aim essentially to find food, mates, resting sites, or avoid predation. Distances moved are very variable among species and may also differ depending on sex or age at the intraspecific scale. Despite a large panel of studies on odonate activities near waterbodies, little is known about their movements and behaviour in the surrounding landscape matrix. This knowledge is, however, crucial to support management schemes of pond networks and allow improvement of connectivity between them. In this study, 87 individuals of the large dragonfly Anax imperator were identified with a unique code on the wings and monitored visually on five ponds during summers 2017 and 2018. Simultaneously, 54 individuals were equipped with radio transmitters and tracked for up to 15 days. We built Cormack Jolly Seber models to test which factors are important for movement and survival of individuals, and calculated home ranges. Additionally, we performed a step selection analysis on the telemetry data to identify the terrestrial habitats selected by A. imperator at the interface between a rural area and a suburban area in north‐western France. A reduction of the survival rate was observed on the day immediately following capture regardless of the marking method. Individuals equipped with radio transmitters had a lower estimated daily survival (0.78; 95% confidence interval = 0.70–0.85) compared to wing‐marked individuals (0.89; 95% confidence interval = 0.85–0.92). Wing loading and age were the main variables influencing dragonfly survival for both methods. The probability of movement between ponds was similar for both sexes, but radio‐tracking data showed that females moved significantly further away in the landscape matrix than males, with one female detected up to 1, 902 m away from the release pond. Females also had a larger home range (mean 95% kernel: 50 ha) than males (mean 95% kernel: 5 ha). Reproductive behaviour of males and flying behaviour of females were positively related to air temperature. Individuals of both sexes were present on ponds more often than in all other habitats whatever their activity. High trees were the preferred place to rest when air temperatures were low, especially for females. Overall, this study highlights the importance of integrating neighbouring trees in management schemes of ponds. It also confirms that preservation of pond networks must include on several hectares of land around ponds to meet the aquatic and terrestrial needs of amphibious organisms such as odonates. Our radio‐tracking data provide a basis for further studies on the persistence of odonate meta‐populations in fragmented landscapes.